Christian Addiction: The Metaphor of Debt-Bondage in Roman Theology - McCracken, Lucas (Journal of the American Academy of Religion, 2023)
What exactly is addiction? Scholars, clinicians, and addicts themselves consistently arrive at a fork in the road in their respective quests for the meaning of addiction: choice or compulsion, crime or disease? Despite these many inquiries, one important aspect of addiction's past remains unexamined - its deep theological history. Christian theologians writing in Latin from the second to the seventeenth century used the term addiction metaphorically to describe the sinful human condition. In this article, I uncover the genesis and development of the Christian addiction metaphor in the writings of Roman theologians Tertullian, Ambrose, and Augustine. I analyze their theologies of addiction to show how the language and logic of Roman pecuniary jurisprudence structures their thinking about sin, salvation, and free will. To conclude, I suggest that the disease-crime ambivalence constitutive of our contemporary understanding of addiction originated in their oxymoronic definition of sin as both generational enslavement and willful servitude.